Marketization strategies and the influence of business on the management of child welfare agencies. Issue 2 (15th March 2018) - Robichau, Robbie Waters; Wang, Lili
ABSTRACT: Nonprofit organizations frequently face external pressures like marketization and governmentalization as well as internal pressures like normative and value expectations on how they should behavior. Using survey data from approximately 150 child welfare administrators, we explore how these pressures combine to influence the adoption of business management practices. Evidence shows that the influence of the business community is persuading managers to implement business strategies while government control and funding have less predictive power on management practices. Surprisingly, a nonprofit mindset has no effect on the likelihood of using business-like management strategies. We conclude with implications and make suggestions for further research.